Guts : the true stories behind Hatchet and the Brian books - Paulsen, Gary. (New York : Delacorte Press, 2001)
The author relates incidents in his life and how they inspired parts of his books about the character, Brian Robeson.
2 6 8 9 13 16 18 19 20 21 25 26 28 29 30 31 32 34 39
Keywords: Paulsen, Gary -- Juvenile literature; Authors, American -- 20th century -- Biography -- Juvenile literature; Children's stories -- Authorship -- Juvenile literature; Paulsen, Gary; Authors, American; Young Hoosier Book Award Nominee 2003-2004